"It's Just a Matter of Adjustment": Residents' Perceptions and the Potential for Low-impact Home Practices. Issue 3 (2nd July 2016) - Hagbert, Pernilla
Abstract: In addition to material, spatial and thermal standards and norms that influence the resource intensity of home environments, a key indicator of the environmental impact related to housing is found in residents' ways of life. Of interest to the study presented in this paper is how residents' perceptions of home and living standards relate to opinions on environmental issues and the reduction of resource use, exploring the potential and willingness to engage in low-impact ways of living. Empirical material from a questionnaire ( n  = 156) and interview study ( n  = 22) with residents in a tenant-owned housing association in Sweden provides insights into conventions and perceptions surrounding practices primarily linked to voluntary simplicity, living smaller as well as sharing spaces and resources. The study emphasizes the need for understanding residents' perspectives and the implications this might have for targeting the resource intensity of homes in future development and policy.